2010
DOI: 10.1186/1477-5956-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of human Wharton's jelly cells during in vitro expansion

Abstract: BackgroundThe human umbilical cord contains mucoid connective tissue and fibroblast-like cells. These cells named Wharton's jelly cells, (WJCs) display properties similar to mesenchymal stem cells therefore representing a rich source of primitive cells to be potentially used in regenerative medicine.ResultsTo better understand their self-renewal and potential in vitro expansion capacity, a reference 2D map was constructed as a proteomic data set. 158 unique proteins were identified. More than 30% of these prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 54 publications
4
59
0
3
Order By: Relevance
“…After ELF-MF treatment, in three different exposure times (5, 10, and 15 days, respectively) SH-SY5Y cells were harvested and resolved by 2D-PAGE according to procedures described previously [Angelucci et al, 2010]. In order to create a master gel representative of all conditions analyzed, 3 different gel runs for each control and treated samples were performed and then subjected to image analysis with Image Master 2D platinum software (GE Healthcare formerly Amersham Biotech, Uppsala, Sweden).…”
Section: Proteome Analysismentioning
confidence: 99%
“…After ELF-MF treatment, in three different exposure times (5, 10, and 15 days, respectively) SH-SY5Y cells were harvested and resolved by 2D-PAGE according to procedures described previously [Angelucci et al, 2010]. In order to create a master gel representative of all conditions analyzed, 3 different gel runs for each control and treated samples were performed and then subjected to image analysis with Image Master 2D platinum software (GE Healthcare formerly Amersham Biotech, Uppsala, Sweden).…”
Section: Proteome Analysismentioning
confidence: 99%
“…Cells were cultured exchanging the medium every 3-4 days until reaching confluence. Adherent cells were detached with 0.05 % trypsin-EDTA, counted by Trypan Blue exclusion test, and re-seeded at 3000 cells/cm 2 to reach the 90 % of confluence after 3-4 population doublings [30].…”
Section: Cell Isolation and Cell Culturementioning
confidence: 99%
“…These results could lead to a new reproductive therapy utilizing human umbilical cord MSCs as well as provide a novel in vitro model for investigating the molecular mechanisms regulating development of the mammalian germ cell lineage [37] . Proteomic analyses of human MSCs from Wharton' s jelly during in vitro expansion have demonstrated their potential capacity for self-renewal and in vitro expansion [38] . More than 30% of 158 proteins identified by these analyses belong to the cytoskeleton complex.…”
Section: Wharton's Jellymentioning
confidence: 99%
“…However, several proteins were no longer expressed after the 2nd in vitro passage, suggesting the proliferative potency of these cells was reduced after the initial in vitro stage. This important study provides an essential step for gaining an understanding of the molecular properties of Wharton's jelly cells [38] . Obstetric parameters, including the gender of the baby, birth weight, the age of the mother at delivery, gestational stage at parturition and mode of delivery were examined by Penolazzi et al [39] who found that osteoblastic potential was not influenced by the baby's gender and mode of delivery.…”
Section: Wharton's Jellymentioning
confidence: 99%